2015
DOI: 10.1128/jvi.03360-14
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of W781V and W780V Mutations in Helix N of Herpes Simplex Virus 1 and Human Cytomegalovirus DNA Polymerases on Antiviral Drug Susceptibility

Abstract: DNA polymerases of the Herpesviridae and bacteriophage RB69 belong to the ␣-like DNA polymerase family. In spite of similarities in structure and function, the RB69 enzyme is relatively resistant to foscarnet, requiring the mutation V478W in helix N to promote the closed conformation of the enzyme to make it susceptible to the antiviral. Here, we generated recombinant herpes simplex virus 1 (HSV-1) and human cytomegalovirus (HCMV) mutants harboring the revertant in UL30 (W781V) and UL54 (W780V) DNA polymerases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…, the IC 50 of FOS for VZV DNApol was measured bellow 1 μM (49) while in another study, an IC 50 of 180 nM was observed (51). In contrast, K I values ranging from 300 nM to 3.5 μM were obtained with HCMV UL54 DNApol (62,74,76,78). This difference in inhibitory effects might be due to the assay used, its sensitivity or to the quality of the protein purification.…”
Section: Structural Features Of Dna Polymerase B Familymentioning
confidence: 87%
See 1 more Smart Citation
“…, the IC 50 of FOS for VZV DNApol was measured bellow 1 μM (49) while in another study, an IC 50 of 180 nM was observed (51). In contrast, K I values ranging from 300 nM to 3.5 μM were obtained with HCMV UL54 DNApol (62,74,76,78). This difference in inhibitory effects might be due to the assay used, its sensitivity or to the quality of the protein purification.…”
Section: Structural Features Of Dna Polymerase B Familymentioning
confidence: 87%
“…investigated the effects of W780V in HCMV UL54 and W781V in HSV-1 UL30, which confer resistance to FOS, GCV and/or ACV (76). In HSV-1 UL30, W781V increased the K I from 0.04 to 1.8 μM (45-fold), while in HCMV UL54, W780V increased the K I from 0.55 to 2.7 μM (4.9-fold).…”
Section: Amino Acid Changes Conferring Drug-resistance Phenotypementioning
confidence: 99%
“…The replicative capacities of HSV-1 and HCMV strains that harbored mutations in the DNA polymerase were reduced compared to those of their respective WT strains when determined by RTCA. Furthermore, we have already demonstrated that there was good concordance between viral replicative capacity determined by RTCA and genome copy numbers in cell lysates measured by real-time PCR for recombinant WT and mutant HSV-1 strains in Vero cells (38). The RTCA technology has the advantages of requiring less work and a shorter manipulation time to evaluate the viral replicative capacities of HSV-1 and HCMV strains than the measurement of virus yields by classical plaque assays or intracellular genome copy numbers by real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some mutations with a resistance index of less than 2 are considered either to confer a reduction of susceptibility to HCMV antiviral drugs or to have no effect on drug susceptibility. For example, A505V, T552N, Q578L, I726V/T, L802V, and L862F mutations are considered to be associated with a lower drug susceptibility, because the majority of them are located within conserved sites of DNA polymerase; some are located at the same position than confirmed resistance‐associated amino acid changes, and all of them have been observed in patients experiencing antiviral treatment failure .…”
Section: Human Cytomegalovirus Drug Resistancementioning
confidence: 99%
“…Moreover, resistance mutations in UL97 and/or UL54 have been associated with treatment failure and progression of HCMV disease and also with poor outcome and in some cases with an attributable mortality of almost 2% . In both pediatric and adult allo‐HSCT recipients, several resistance mutations have been reported, and while some are shared with other immunocompromised individuals , others are only found in HSCT recipients (Tables and ).…”
Section: Human Cytomegalovirus Drug Resistancementioning
confidence: 99%